ESG, environmental innovation, and corporate profitability: Evidence of direct and lagged effects from Indonesia - Tarsisius Renald Suganda; Dorothy Srikandi Halim; Probowo Erawan Sastroredjo; Boymurodov Farrukh Farkhod ugli (Postgraduate Program Merdeka University, 2026)
This study investigates whether environmental innovation serves as a mechanism through which ESG performance influences corporate profitability in an emerging market context. While prior studies showed a direct association between ESG and firm performance, evidence on the mediating role of environmental innovation remains limited, particularly in Indonesia. Using panel data from all non-financial firms listed on the Indonesia Stock Exchange during 2012-2023, this study employs fixed-effects regression, mediation analysis, and lagged-effect testing. ESG performance is measured by ESG scores, environmental innovation is proxied by environmental innovation scores, and profitability is assessed using return on assets (ROA) and return on equity (ROE). The results indicate that ESG performance positively affects both environmental innovation and profitability. Environmental innovation significantly improves ROE and shows a weaker contemporaneous effect on ROA, while lagged analyses show positive impacts on both profitability measures. The findings extend the ESG-performance literature by demonstrating that environmental innovation acts as a transmission mechanism through which ESG performance generates financial benefits over time in an emerging market setting. For managers and policymakers, the results underscore the importance of aligning ESG initiatives with environmental innovation strategies and supportive regulatory incentives to enhance long-term profitability and sustainable value creation.